Broadcasting Hollywood : the struggle over feature films on early TV - Porst, Jennifer (Rutgers University Press, 2021)
"Broadcasting Hollywood: The Struggle Over Feature Films on Early Television uses extensive archival research into the files of studios, networks, advertising agencies, unions and guilds, theatre associations, the FCC, and key legal cases to analyze the tensions and synergies between the film and television industries in the early years of television. This analysis of the case study of the struggle over Hollywood's feature films appearing on television in the 1940s and 1950s illustrates that the notion of an industry misunderstands the complex array of stakeholders who work in and profit from a media sector, and models a variegated examination of the history of media industries. Ultimately, it draws a parallel to the contemporary period and the introduction of digital media to highlight the fact that history repeats itself and can therefore play a key role in helping media industry scholars and practitioners to understand and navigate contemporary industrial phenomena"--